2021
DOI: 10.5114/jcb.2021.103582
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric comparison of computed tomography-guided iodine-125 seed implantation assisted with and without three-dimensional printing non-coplanar template in locally recurrent rectal cancer: a propensity score matching study

Abstract: Purpose To compare post-implant dosimetric parameters of computed tomography (CT)-guided radioactive iodine-125 ( 125 I) seed (RIS) implantation assisted with and without three-dimensional printing non-coplanar template (3D-PNCT) in locally recurrent rectal cancer (LRRC). Material and methods One hundred and fifty-five LRRC patients treated by CT-guided RIS implantation assisted with or without 3D-PNCT from October 2003 to May 2019 were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Different from the previous studies in which the SABT was performed with free hand guided by CT, in our study, 9 patients were treated with SABT assisted by the 3D-printing template and guided by the CT. Wang et al reported that the template assistance signi cantly improved the accuracy and e cacy of SABT for the recurrent rectal cancer (30). In this study, the 3D-template-assisted and CT-guided SABT showed a trend of better local control compared with CT-guided SABT, but the differences were insigni cant (HR, 0.42, P=0.410) possibly due to that the sample size of the patients receiving advanced SABT was small.…”
Section: Adverse Eventsmentioning
confidence: 61%
“…Different from the previous studies in which the SABT was performed with free hand guided by CT, in our study, 9 patients were treated with SABT assisted by the 3D-printing template and guided by the CT. Wang et al reported that the template assistance signi cantly improved the accuracy and e cacy of SABT for the recurrent rectal cancer (30). In this study, the 3D-template-assisted and CT-guided SABT showed a trend of better local control compared with CT-guided SABT, but the differences were insigni cant (HR, 0.42, P=0.410) possibly due to that the sample size of the patients receiving advanced SABT was small.…”
Section: Adverse Eventsmentioning
confidence: 61%
“…22,23 Furthermore, the anatomy is distorted because of the intervention of the template and applicator, making preplanning necessary to achieve optimal needle track and isodose distribution. Several articles have studied the use of a 3D-printed template for particle therapy, [24][25][26] proposing the superiority of exact orientation and localization of inserted needles and considering it a result-oriented and accurate auxiliary tool in brachytherapy. In this study, we utilized an offline preplan based on CT images 1 week before the treatment to design and print the template.…”
Section: Discussionmentioning
confidence: 99%
“…The results from previous studies and ours suggested that SABT had a good efficacy for HNACC. Interestingly, the local control seemed better in our and Zhang’s study than in Ashamalla’s study, which was probably attributed to the application of template and CT. Our previous work indicated that template assistance significantly improved the accuracy and efficacy of SABT [ 30 ]. Additionally, 3D-PNCT is superior to the 3D-PCT in some aspects.…”
Section: Discussionmentioning
confidence: 99%